Analysis Of Restriction Rules Of Gross Tonnage Fishing Ship On The Sunda Sea Coast (Maritime Park: Journal of Maritime Technology and Society, 2022)
The Sunda Strait has a significant enough fishery potential in Indonesia. Fish catches from the Sunda Strait are landed in Pandeglang Regency, one of which is at the Labuan Coastal Fishing Port. The types of fish that are targeted for catching are mackerel and tuna. The high selling price of fish causes fishing operations to continue to be improved. Fishing operations that continue to increase can lead to a scarcity of fishery resources. Therefore, it is necessary to study the rate of fish resource utilization to determine their status. This study aimed to evaluate the rate of exploitation of tuna in the Sunda Strait based on fish catch data on 30 GT vessels and analyze it using policies issued by the Indonesian government. In this study, a simple linear regression method was used. Result of analysis, in 2025, the fish stock is only 21,682 ton, while the number of fish taken is 66,497 ton, which means that in 2025 there will be no more fish because the fish stock has run out and cannot meet the number of fish that needs to be taken.
Keywords: Tuna; Ship Gross Tonnage; Sunda Strait